2010
DOI: 10.1080/00140139.2010.502252
|View full text |Cite
|
Sign up to set email alerts
|

Continuous assessment of work activities and posture in long-term care nurses

Abstract: The high prevalence of low back injuries in nursing has prompted the use of mechanical lift assists while overall assessment of activities and postures remains limited. The purpose of this study was to chronicle trunk posture and work tasks of long-term healthcare professionals. An inclinometer monitored trunk posture for 27 workers, 20 of whom were also observed continuously throughout their shift. Patient lifts and transfers accounted for less than 4% of the shift while patient care, unloaded standing and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
54
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 34 publications
1
54
0
1
Order By: Relevance
“…In this context, many studies have examined manual patient transfers and identified them as a risk factor (Engkvist et al , 2000; Byrns et al , 2004). However, patient transfers take up <4% of a work shift (Hodder et al , 2010) and nurses have many other types of work to perform, such as washing patients, making beds, or changing dressings (Harber et al , 1987; Freitag et al , 2007). In a previous study, we found that nurses often bend forward (sagittal trunk inclination) when performing the pre-mentioned activities or work for extended periods in an inclined posture (static trunk inclination) (Freitag et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, many studies have examined manual patient transfers and identified them as a risk factor (Engkvist et al , 2000; Byrns et al , 2004). However, patient transfers take up <4% of a work shift (Hodder et al , 2010) and nurses have many other types of work to perform, such as washing patients, making beds, or changing dressings (Harber et al , 1987; Freitag et al , 2007). In a previous study, we found that nurses often bend forward (sagittal trunk inclination) when performing the pre-mentioned activities or work for extended periods in an inclined posture (static trunk inclination) (Freitag et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…39,51,57 Previous studies have used a variety of devices for postural monitoring. 4,13,18,48,58 A common problem found in postural-monitoring devices used during daily activities is the trade-off between portability and accuracy of measurements. Instruments such as the moment T T STUDY DESIGN: Feasibility randomized controlled trial.…”
mentioning
confidence: 99%
“…[8][9][10] Most physical risks contributing to LBP in nurses are focused on occupational factors such as extent of bending and lifting. [11] A range of personal physical factors, including reduced cardiovascular fitness, [12] poor back muscle endurance, [13] altered motor control patterns, [14] poor spinal posture, [15] and reduced sagittal range of motion [16,17] have been found in various LBP populations. Further, lifestyle factors such as physical inactivity [18] and high levels of vigorous physical activity [19] have been associated with LBP.…”
Section: Introductionmentioning
confidence: 99%